Impact of control on innovation: the case of franchising. Issue 7 (9th July 2018) - Karmeni, Kerim; de la Villarmois, Olivier; Beldi, Adel
Abstract : Purpose: The purpose of this paper is to investigate the relationship between organizational control and innovation. The authors address two questions: "First, does the organizational control have a positive impact on innovation within a franchise network? Second, if such positive relationship exists, how we can explain it?" Design/methodology/approach: The study used a survey data of 106 outlets belonging to franchise networks in France, using partial least squares and mobilizing an analysis of mediating effects. Findings: Organizational control is positively related to innovation; this positive relationship can be partly explained by the mediating effect of knowledge creation. Research limitations/implications: Taking care to use appropriate techniques that guarantee a higher response rate (e.g. following up contacts after the initial request, phoning before sending the questionnaire), this study could be extended to other forms of organization, such as cooperatives or MNCs, to generalize the explanation of the positive impact of control on innovation through the mediating effect of knowledge creation. Practical implications: The empirical results show that control encourages knowledge creation and innovation, which is a strong argument for franchisors to persuade franchisees of the necessity and utility of implementing organizational control. Moreover, the results constitute a practical tool to help managers making decision regarding innovation management. Innovation success can be improved by paying attention to the organizational control and deploying a combination of different control mechanisms including process, outcome and social. Originality/value: To the authors' knowledge, this is the first study to investigate both direct and indirect effects of organizational control on innovation. The authors contribute by explaining the complex relationship between control and innovation.